Targeting the Nutritional Value of Proteins From Legumes By-Products Through Mild Extraction Technologies - Prandi, Barbara; Zurlini, Chiara; Maria, Cigognini Ilaria; Cutroneo, Sara; Di Massimo, Martina; Bondi, Marika; Brutti, Andrea; Sforza, Stefano; Tedeschi, Tullia (Frontiers in Nutrition, 2021)
Legumes have been known for centuries for their good nutritional properties. Unfortunately, during processing, from 5 to 25% of this production is wasted, generating by-products that can still be a rich source of useful compounds, such as proteins, which can still be used in food and feed formulations. The choice of the extraction technique is important to preserve the nutritional value of proteins since drastic conditions of pH and/or temperature could damage them. In this work, two mild extraction techniques (direct assisted extraction—DAE and enzymatic assisted extraction—EAE) were applied for protein extraction from legume by-products obtained from agro-industrial processes. The quality of proteins was evaluated considering protein integrity [SDS-PAGE, degree of hydrolysis (DH), free amino acid content, racemization degree] and nutritional features [amino acid score (AAS), digestibility]. Direct assisted extraction is the technique that has best preserved protein integrity (1–5% DH and free amino acid content <1%), The digestibility of proteins extracted with EAE is higher (no protein bands detected in SDS-PAGE) than with the one of DAE extracts, making this technique particularly suitable for those food and feed formulation were a high digestibility of proteins is required.